Effects of Bi3+ doping on charge ordering and high magnetic field phase diagram of Nd0.6-xBixCa0.4MnO3. (January 2020) - Shang, C.; Xia, Z.C.; Zhao, B.; Liu, D.W.; Wang, Y.Q.; Su, Y.L.
Graphical abstract: Highlights: The charge ordering (CO) phase in Nd0.6- x Bi x Ca0.4 MnO3 is enhanced with Bi 3+ doping. The enhancement of CO phase is explained by the s-p hybridization model. Pulsed high magnetic fields up to 50 T were used to study the CO phase melting. H C - T phase diagrams of Nd0.6- x Bi x Ca0.4 MnO3 (0 ≤ x ≤ 0.4) were obtained. Abstract: We report the doping effects and pulsed high magnetic field-induced charge ordering to ferromagnetic phase transitions in manganites Nd0.6- x Bi x Ca0.4 MnO3 (0 ≤ x ≤ 0.4). The experimental results reveal that the charge ordering is significantly enhanced upon Bi 3+ doping, and the charge ordering temperature increases with increasing Bi 3+ content. With applying pulsed high magnetic field, the charge ordering phase collapses into ferromagnetic phase through a metamagnetic transition. The phase diagram of Nd0.6- x Bi x Ca0.4 MnO3 has been determined by the high magnetic field studies, in which the charge ordering and ferromagnetic phase boundary is clearly figured out. The critical fields for melting the charge ordering phase of Nd0.6- x Bi x Ca0.4 MnO3 increase significantly with increasing Bi 3+ content, which is revealed to reach up to 33.5 T for the sample with x = 0.3. Based on the hybridization between Bi-6s orbitals and O-2p orbitals, we assume that the 6s 2 lone-pair character of Bi 3+ plays a crucial role in favoring the charge ordering in Nd0.6- x Bi x Ca0.4 MnO3 (0 ≤ x ≤ 0.4).